DESIGNING OF DEVICES ON THE BASIS OF EXPERT SYSTEM TECHNOLOGIES - V. M. Pashkevich; M. N. Mironova (Наука и техника)
The paper considers problems pertaining to designing of accessories for metal-cutting machine tools. The approach based on expert systems technologies has been used in the paper. The paper describes a hybrid expert system and its knowledge is presented in the form of production rules. The paper studies knowledge bases intended for a selection of basing scheme and also for a selection of clamping elements and power drives of machine-tool accessories. Variable conditions of database rules are described in the paper. The paper presents an example of selecting a structure of a power mechanism for a machine tool accessory. The possibility to use an expert system in the integrated systems of automated machine-tool accessory designing is revealed  in the paper.